Pengaruh Struktur Kepemilikan dan Kinerja Perusahaan terhadap Kebijakan Dividen - Maria Claudia Karina; Darsono Darsono (Diponegoro Journal of Accounting, 2014)
The purpose of this research is to examine the effect of ownership structure and corporate performance on dividend policy. Ownership structure used in this study is managerial ownership, while the performance of companies include free cash flow, growth in assets, profitability, and leverage as an independent variable, firm size as a control variable, and dividends per share as the dependent variable. The population in this study are all companies listed on the Indonesia Stock Exchange in 2010-2012. The data that was used in this research was secondary data and selected by using purposive sampling method. Analysis model using multiple linear regression analysis. The sample used in this study were 152 companies. The analysis showed that profitability is positive and significant effect on dividend policy, while managerial ownership, free cash flow, asset growth, and leverage does not significantly affect to dividend policy.